Forward Osmosis for Produced Water Treatment: A Comprehensive Review - Shafiq Mohd Hizam; Muhammad Roil Bilad; Nik Abdul Hadi Md Nordin; Norazanita Shamsuddin (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2021)
During crude oil and natural gas extraction from a reservoir, a large amount of water is also produced. The water fraction contains oil, grease, organic and inorganic constituents, called produced water (PW). Over the years, efficient treatment of PW has been concerned. PW has been treated with various technologies, namely floatation, filtration, coagulation/flocculation, or biological processes. Those technologies were assembled to achieve discharge standards while minimizing the cost. Exploration of membrane-based technologies for the treatment of PW has recently been reported, including the emerging forward osmosis (FO) process. This paper reviews the research progress on the FO process for PW treatment. A brief introduction to the traditional treatment technologies is first provided. Next, the basics of the FO process and research progress on the application of FO on PW treatment are discussed. Finally, techniques for fouling control in FO are reviewed, namely osmotic backwashing, ultrasound, chemical cleaning, and air sparging.